Enhancement of Labneh Quality by Laser-Induced Modulation of Lactocaseibacillus casei NRRL B-1922 - Fouad M. F. Elshaghabee; Ahmed El-Hussein; Mahmoud S. M. Mohamed (Fermentation, 2022)
Labneh is positioned in the top ranking of the bestselling dairy products all over the world due to its health benefits and delicious taste. Labneh production depends mainly on probiotic bacteria in the fermentation of milk. Probiotic bacteria have many health benefits, which are driven by their selective bioactive metabolites that quantitively affect the fermentation products. The current investigation aimed to study the implementation of photobiomodulation through the irradiation of Lacticaseibacillus casei NRRL-B-1922 by a He–Ne laser (630 nm) with different laser doses (3, 6 & 12 J/cm2) prior to milk fermentation. This procedure sought to improve the probiotic bacteria’s activities while enhancing the labneh’s characteristics and consequently produce a more favorable labneh product with better marketing qualities. The photobiostimulated bacterial starter was found to induce increased titratable acidity with the moisture reduction of the labneh product under cold storage conditions for 20 days. The effect was most prominent when using a 12 J/cm2 laser dose. The flavor-aiding components, mainly diacetyl and acetaldehyde compounds, and sensory scores were increased in the labneh produced by irradiated L. casei when compared to the non-radiated probiotic culture after storing the products under cold conditions for 20 consecutive days. Moreover, the antioxidant and proteolytic activities of labneh produced by treated L. casei (12 J/cm2 laser dose) after cold storage were significantly elevated by 41 and 14%, respectively. In conclusion, we can report significantly improved selected characteristics in the final products after the employment of photobiomodulation process, the potential application of this concept on the industrial scale, and its implications on lengthening the product shelf life with improved qualities.